2014
DOI: 10.1186/1471-2458-14-271
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of risk and protective factors related to suicide ideation among residents and specialists in academic medicine

Abstract: BackgroundPhysicians have an elevated risk of experiencing suicidal thoughts, which might be due to work-related factors. However, the hierarchical work positions as well as work-related health differ among resident and specialist physicians. As such, the correlates of suicide ideation may also vary between these two groups.MethodsIn the present study, work- and health-related factors and their association with suicidal thoughts among residents (n = 234) and specialists (n = 813) working at a university hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…Mortality rate by almost all causes of death, except suicide, is however lower for physicians than for the general audience [8] [26], which is in agreement with the healthy worker's effect [8].…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…Mortality rate by almost all causes of death, except suicide, is however lower for physicians than for the general audience [8] [26], which is in agreement with the healthy worker's effect [8].…”
Section: Introductionsupporting
confidence: 57%
“…Physicians usually commit suicide in higher frequency compared to the general population [6] [7] [8]. Thus, the decrease of suicide mortality among physicians should be the main purpose of this working class to change this situation [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16][17] Studies have suggested that work-related stressors are a factor, with work-related stress having an impact on the risk for suicidal ideation among physicians in training and in practice. 13,16 The CRCR focused on the learning environment as a modifiable factor that may be transformed to support the physician in training. We selected appreciative inquiry for our discussion, since we wanted to build the system for promoting resident wellness on the existing positive aspects of the learning environment.…”
Section: Discussionmentioning
confidence: 99%